PSYCHOLOGICAL AND DIDACTIC FUNDAMENTALS FOR FUTURE SEAFARERS’ ENGLISH-LANGUAGE COMMUNICATION TEACHING - Ogorodnik, Natalia (International Journal of Innovative Technologies in Social Science, 2020)
Among the basic principles of the English-language communication skills development for future seafarers is the principle of consciousness. Being implemented in a teaching and learning process it provides understanding as a fundamental component of the future seafarers’ professional competence. As a result, all the aspects of language knowledge (linguistic, speech, and linguo-sociocultural issues) are processed by the students consciously. They also become able to communicate in full compliance with a communicative situation and a specific cultural context. Moreover, effective learning tactics and strategies that students master reasonably are expected to facilitate them in their further life-long learning process. The students’ age, which is characterized by psychologists as a young adulthood, has a tendency for intellectual development. According to the scientists, at this particular period of time the change of a development focus takes its place, caused by a crucial point in human evolution. The sophisticated identity crisis of 17-year-olds occurs owing to the mismatch between the individual development and the social situation. Another situation, mediated by the educational and professional activity, as a leading one for this age is recognized as a factor that activates the comprehensive personality transformation and starts a new stage of mental development in adolescence, resulting in the intellectualization of all the cognitive processes, and therefore to a more deliberate mastery of knowledge.